Underside of independence politics Filipino reactions to anti-Filipino riots in the United States - Okada, Taihei (Philippine Studies: Historical and Ethnographic Viewpoints)
This article reexamines the historical implications of Philippine independence politics in the first half of the 1930s. It looks into the reactions of Filipino elites toward the grave plight of Filipino migrants in the United States and the anti-Filipino riots there. Exclusion measures intended to bar the entry of Filipino migrants to the United States made it virtually impossible for Filipino elites to discuss these issues and confront American racism in their formal negotiations with the Americans. The absence of such confrontation left the benevolence of US colonialism unchallenged, even as the Philippines took a step closer to political independence.